Effectiveness of online integrative trans-diagnostic treatment on internet addiction and high-risk behaviors in female adolescents with borderline personality disorder with comorbid depressive disorder - Mohamadpour, Fahimeh; Mohammadi, Nurallah (Frontiers in Psychiatry, 2024)
Background: Based on research, borderline personality disorder is associated with many behavioral and emotional problems, including Internet addiction and high-risk behaviors. On the other hand, integrative trans-diagnostic treatment, by targeting trans-diagnostic factors in emotional pathology, is considered a suitable treatment for comorbid psychological pathologies. Therefore, the aim of the current research was to investigate the effectiveness of online integrative trans-diagnostic treatment on the internet addiction and high-risk behaviors in adolescents with borderline personality disorder.The current research was applied and quasi-experimental. The research sample included 40 female adolescents with borderline personality disorder who were randomly divided into two groups of 20 people. The criteria for entering the research included the age range of 12 to 18 years, female, confirmation of the disease by a psychologist, not receiving other psychological treatments in the last three months, and having a smartphone to participate in the online group. Substance abuse, any serious mental and physical illness/disorder that interferes with treatment, and failure to attend more than two sessions in therapy sessions were some of the exclusion criteria.The participants were tested on the scales of internet addiction and high-risk behaviors. Then, the treatment plan was presented to the participants of the experimental group online in 9 two-hour sessions. The control group was placed on the waiting list until the completion of the treatment sessions and the post-test implementation. Then, their scores were measured, after completing the treatment, and a three-month follow-up period. Descriptive statistics and covariance test were used to analyze the data.Results: Patients showed a clear improvement in the severity of internet addiction and high-risk behavior symptoms. So that the scores in the experimental group after receiving the treatment, as well as after a three-month follow-up period, were significantly reduced (p<0.001).Conclusions: These results show that online integrative trans-diagnostic therapy can be an effective treatment option for reducing some symptoms of risky behaviors and internet addiction in adolescents with borderline personality disorder and should be studied further.